SCREENING OF ANTI-BIOFILM, ANTI-QUORUM SENSING ACTIVITY FROM METHANOLIC EXTRACT OF Plectranthus amboinicus (Lour) - R. NANCY IMMACULATE MARY; N. BANU (International Journal of Pharma and Bio Sciences, 2015)
Quorum sensing (QS) is well known for bacterial cell to cell dependent mechanism and its stimulus response are correlated to population density. Quorum sensing inhibition can reduced the risk of microbial pathogenicity in all infection. In this study methanolic leaf extract of Plectranthus amboinicus was assessed for its anti quorum sensing activity against Acyl Homoserine Lactone (AHL)-dependent virulence factor inhibition in all bacterial pathogens [Serratia marcescens, Pseudomonas aeruginosa, Vibrio harveyi (MTCC 7771), Hafnia alvei (MTCC 1426)] at the concentration of 50mg/ml. In addition the methanolic leaf extract Plectrantus amboinicus showed no growth inhibitory effect on bacterial pathogens. The methanolic leaf extract of Plectrantus amboinicus have also inhibited the rhamnolipid production in Pseudomonas aeruginosa and controlled the swimming and swarming motility in Serratia marcescens. In Vibrio harveyi (MTTC 7771) the bioluminescence was controlled by Plectranthus amboinicus at the concentration of 50mg/ml. Hence it was envisaged that the methanolic leaf extract of Plectrantus amboinicus could pave the way to prevent quorum sensing (QS) mediated bacterial infections.